History in the void: Giuseppe Samonà’s 1967 proposal for Montecitorio competition - Vujičić, Lejla (Journal of Architecture and Urbanism, 2024)
Giuseppe Samonà was one of the most influential figures in 20th century Italian architecture and urban culture. In 1967, Samonà and his team submitted a competition proposal for the extension of the Camera dei deputati in Rome, considered by many to be one of the most significant and conceptually mature projects of his career. By examining the design and the report appended to the competition submittal the author explores the concept of the void that is the backbone of the project and finds that it has a twofold interpretation. Apart from the obvious physical manifestation of emptying, the void is also a meditative device, an incorporeal entity that relies on the body of the new insert to show the complexity of the history of the Roman site. It is in this inversion of the usual interpretation of the concept of void as being independent nothingness that allure of the project itself lies. By presenting the archival material and contemporary research, the author brings into focus a part of Samonà’s extraordinary contribution to the architecture and urban culture of the 20th century that surprisingly remains unrevealed to non-Italian audiences.